Protecting The Big Easy From the Next Big One. - Sweet, W.
The US Army Corps of Engineers holds the primary responsibility for the construction, maintenance, and operational supervision of the New Orleans levee system. After hurricane Katrina, Congress told the corps to restore the system to at least pre-Katrina levels. But now comes the hard part. Congress has told the corps that its next task is to build up the New Orleans hurricane protection system to shield the city from all but a 100-year storm - a hurricane of a ferocity that would be expected, statistically, to occur only once in a century
Keywords: 100 year storm; Interagency Performance Evaluation Task Force; New Orleans; US Army Corps of Engineers; Hurricane Katrina; Hurricane protection system; Levee system; Operational supervision